A Preliminary Study on Information Systems Bachelor Graduates’ Intention to Pursue a Master Program in Computing - Marin FOTACHE; Florin DUMITRIU; Nicolai ROMANOV (Communications of International Proceedings, 2021)
There is a consistent body of literature on the student dropout and retention in computing education, but less attention has been paid to the bachelor graduates who intend (or not) to continue their studies with a master’s degree program in a computing-related area, i.e., graduates who remain “loyal” to computing education. This paper examines the relationships between the intention of Information Systems bachelor graduates to pursue a master program in computing at the same faculty and a series of predictors related to their academic performance and background, i.e., genre, milieu (urban or rural), and the concentration of graduated high-school class. The findings of our research reveal that academic performance could represent an antecedent of students’ intention to continue to study in the computing area, while genre, milieu, and concentration of graduated high school are not significant factors.
Keywords: Information Systems Undergraduate Programs; Graduate/Master Programs in Computing; Enrolment in Computing Programs